1999
DOI: 10.1016/s0378-4320(99)00031-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the interval of serial sections of ovarian tissue in the tissue chopper on the number of isolated caprine preantral follicles

Abstract: The present work investigated the effect of the interval of serial sections of ovarian tissue on the number of isolated preantral follicles in the goat. Goat ovaries were cut in the tissue chopper at eight different intervals. The quality of isolated follicles were evaluated by histology and transmission electron microscopy. Best results were obtained when the ovaries were cut in the tissue chopper at intervals of 75.0 μm (9664 preantral follicles per ovary). Histochemical and ultrastructural analysis showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
45
0
3

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 29 publications
7
45
0
3
Order By: Relevance
“…This effect has already been demonstrated in other species, like caprine [6] and ovine [5]. In the present work, the greatest number of isolated Zebu cow preantral follicles was obtained using the 125 pm interval.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This effect has already been demonstrated in other species, like caprine [6] and ovine [5]. In the present work, the greatest number of isolated Zebu cow preantral follicles was obtained using the 125 pm interval.…”
Section: Discussionsupporting
confidence: 83%
“…Indeed, one of the most efficient methods for isolating a large number of follicles consists of using a tissue chopper [2][3][4]. Recently, however, studies have demonstrated that the best interval for sectioning the ovarian tissue using the tissue chopper can vary according to species [5,6]. In addition to isolating a large number of follicles, a suitable method should preserve the normal follicular morphology after isolation, not only on the structural level, but also on the ultrastructural level [7].…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative analyses of goat preantral follicles in situ (Bezerra et al, 1998 andLucci et al, 1999b) or after isolation (Lucci et al, 1999a) were performed using classical histology and transmission electron microscopy. However, these analyses were performed using only fresh preantral follicles.…”
Section: Discussionmentioning
confidence: 99%
“…A specific mechanical method for the isolation of a great number of intact preantral follicles per ovary was recently developed in the goat (Lucci et al, 1999a). The development of systems which support oocyte growth in vitro is valuable for the conservation of the female genetic pool.…”
Section: Introductionmentioning
confidence: 99%
“…During the past few years the possible exploitation of preantral follicles from domestic animals, by isolation and culture, has received much attention , Jewgenow and Goritz, 1995, Nuttinck et al, 1996, Wandji et al, 1996, Lucci et al, 1999and Cecconi et al, 1999. However, in some studies, the results were not promising possibly due to follicle damage induced by the isolation procedures (Van den Hurk et al, 1997 and Katska and Rynska, 1998).…”
Section: Introductionmentioning
confidence: 99%